A produção do conhecimento da pós-graduação em Educação da Universidade Federal de Sergipe : realidade e possibilidades epistemológicas - Araujo, Maria Gorete Bezerra de (2014)
This research report has the theme |Knowledge Production Analysis of Graduate Studies in Education of the Federal University of Sergipe, in 2009-2011.| The methodological theory behind this work is the dialectical historical materialism, because we understand that this theory presents a categorical complex that allows radically grasp our problem under study. Our empirical field is the Graduate of the Federal University of Sergipe Center where are the empirical sources that are the dissertations of 2009-2011. To characterize this research is adopted the documentary research, trying to discuss the problem of production of knowledge regarding the methodological theories; this scientific production meets the needs and interests of the working class in favor of a quality education. This study shows how problematic the following question: |How do you have the epistemological trends in the production of knowledge of NPGED / UFS, in line Educator Training from 2009 to 2011?| Faced with this question, share the understanding that science is built by formulating hypotheses that may or may not be proven with the completion of studies. So, we set hypothesis, that there is a significant quantity of dissertations in NPGED / UFS, from 2009 to 2011 in line Educator Training: with knowledge and skills that link to the phenomenological hermeneutics trend. Within the above, were traced the objectives of this work based on the issue and in the event that previously listed are: General Objective: To analyze as epistemologically present the production of knowledge, Postgraduate Diploma in Education, UFS, on Line Training educators in the period 2009-2011. The instrument used to collect and analyze the data was the paradigmatic matrix developed by Prof. ° Gamboa. Then the data were analyzed from the methodological categories, and all contradiction and categories of content, design of science, man and education. The research result shows that the Knowledge Production of the Graduate Center NPGED / UFS, from 2009 to 2011, mostly is grounded by the phenomenological trend - hermeneutics. To this trend, the interpretation and understanding are essential in the need that men have to communicate. So the cognitive interest that guides the phenomenological hermeneuticalinvestigations is communication.